Personality Analysis Of The Character Lucas Ford In The Novel In A Blue Moon By Ilana Tan: A Study Of Literary Psychology - Sirait, Raisyicha Mutik (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research specifically aims to describe the personality of the main character Lucas Ford in the novel In a Blue Moon by Ilana Tan. This research uses a qualitative approach with descriptive methods. This type of research uses library, listening and note-taking techniques. His research is to examine the personality aspects of characters in literary works. This approach will provide an overview of the thought process experienced by the main character which is a form of the id, ego and superego personality aspects. The research results show that the personality of the main character in the novel In a Blue Moon by Ilana Tan includes the id, ego and superego.